STUDI KITAB AL-JĀMI’ AL-SAGHĪR MIN AHĀDĪTH AL-BASHĪR AL-NADHĪR KARYA AL-SUYŪTĪ - Anshori, Muhammad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
This paper attempts to examine one of the hadith books which has great influence in the study of hadith, ie al-J?mi al-Sagh?r min Ah?d?th al-Bash?ral-Nadh?r al-Suy?t? (1405 M / 911 H). The book is composed of Arabic alphabets or mu?jam in order to facilitate the search for the matan hadith. Some scholars have paid attention to al-J?mi al-Sagh?r with sharh so it is easy to understand the contents of his hadith content. With the descriptive-analytical method of this paper indicates that the quality of hadith in the book is varied, some are valid, hasan, daif, even false or have no obvious origin. al-Suy?t? is known to be less precise and easy in validating a hadith. The criterion of the validity of hadith is very loosely so that it seems more emphasized aspect of matan than sanad. Of course it is also important but the study of sanad should also be done to balance. al-J?mi ?al-S{agh?r is one of the books referring to many sources of earlier hadith books. Of the several books that exist, the book of hadith is arranged alphabetically so that the reader is easy to find matan hadith directly. In addition there are some traditions that are not arranged alphabetically or alphabetically. al-J?mi al-Sagh?r al-Suy?t? work has contributed in enriching the hadith literature.